2023
DOI: 10.3390/md21070386
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Screening and Antibacterial Mechanism Analysis of Novel Antimicrobial Peptides from Sturgeon (Acipenser ruthenus) Spermary

Abstract: Fish is an important source of antimicrobial peptides. This study aimed to identify and screen antibacterial peptides with excellent antibacterial activity derived from sturgeon spermary peptides (SSPs) and to analyze their antibacterial activity and mechanism. Liquid chromatography-mass spectrometry/mass spectrometry methods were used to analyze and identify peptide sequences, computational prediction tool and molecular docking methods were used for virtual screening of antimicrobial peptides, and finally, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Additionally, some AMPs can penetrate cell membranes to target intracellular processes, further diversifying their mechanisms and reducing the likelihood of resistance [ 18 ]. Additionally, antimicrobial peptides exhibit broad-spectrum activity against various bacteria and have lower toxicity to host cells [ 19 , 20 ]. Being natural substances, they are considered safer and more reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some AMPs can penetrate cell membranes to target intracellular processes, further diversifying their mechanisms and reducing the likelihood of resistance [ 18 ]. Additionally, antimicrobial peptides exhibit broad-spectrum activity against various bacteria and have lower toxicity to host cells [ 19 , 20 ]. Being natural substances, they are considered safer and more reliable.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics have been widely used in livestock industry to treat and prevent microbial infection and promote animal growth. However, large-scale antibiotic use has increased the resistance of pathogenic microorganisms, and the presence of drug residues in feed leads to environmental contamination. There is an additional impact on livestock and poultry immune function, through antibiotics directly inhibiting respiratory activity in immune cells and consequently impairing their phagocytic activity. In an attempt to reduce antibiotic use, antimicrobial peptides (AMPs), which do not easily induce resistance, have been extensive investigated. Study has found that AMP PR-39 is overexpressed in macrophages, thereby inhibiting the activity of intracellular Salmonella enterica serovar Typhimurium . AMPs Epinelicin-1 and Hepcidin reduce the lethality of Riemannia anatipestifer sepsis in ducks .…”
Section: Introductionmentioning
confidence: 99%